The real estate code of ethics: Viable or vaporous? - Conway, Jeremiah (Journal of business ethics, 1982)
Several recent articles in the field of ethics and business have raised questions concerning the viability of professional ethical codes. Are such codes serious, effective tools for promoting and enforcing an ethical standard of behavior? Or do the codes more closely resemble clever, elaborate public-relation ploys? The purpose of this paper is to analyze the content, role and efficacy of one such ethical code, namely, The Code of Ethics of the National Association of Realtors. The paper examines the ethical principles embodied, implicitly or explicitly, in this Code; it tests these principles for coherence, comprehensiveness, clarity and enforce-ability. Furthermore, it seeks to determine whether this Code articulates standards of ethical conduct that are higher than those already required by law and whether the Code successfully translates a general ethical vision down to concrete, everyday real estate practice.